Population dynamics: Species traits and environmental influence - Fowler, C W (Whales, seals, fish, and man : proceedings of the International Symposium on the Biology of Marine Mammals in the North East Atlantic, Troms,̜ Norway, 29 November-1 December 1994, 1995)
The population dynamics of species constitute species level properties that are both genetically and environmentally influenced. General patterns in population dynamics related to life-history strategies result from the expression of genetically based traits. Variability about such patterns is under environmental influence. A correlation between the shape of density-dependence curves and rates of increase per generation is an example of genetically controlled patterns. Deviation from such patterns exemplifies the degree to which the shape of density-dependence curves is related to conditions faced by species interacting with both their biotic and abiotic surroundings. The genetic aspects of both species- and ecosystem-level traits are subject to modification through exploitation. Most resource and ecosystem models fail to account for genetic change produced by harvesting.